HISTOLOGICAL AND STATISTICAL STUDIES ON THE OVARIAN CYCLE OF THE CARAMOTE PRAWN MELICERTUS KERATHURUS (FORSKAL, 1775) (CRUSTACEA DECAPODA) - Hussein, Abdallah Bedeer (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
The two ovaries of the caramote prawn Melicertus kerathurus lie above the hepatopancreas and below the pericardial sinus and the heart. Both ovaries were reduced in general size with white compact and sickle-shaped contents during January- March. Their contents attain gradually a pale green colour in April - June. This stage is an early maturing in which the ovary increased in size and the anterior and middle lobes are developing. When the ovary is immature the surface is relatively smooth and homogenous, but as the organ grows the surface acquires an increasingly irregular ppearance. They contain oocytes and small spherical ova with light-stained cytoplasm free from granules and a conspicuous nucleus. During July -September, mature stage in which the ovary is in a maximal size and filled with vitellogeneic and ripe oocytes. They were dark green. During October- December, the gonad reverted gradually to the immature condition i. e., the ovary undergoes a spent-recovering and was with varying degrees of yellow colour. For each season three ovaries were studied carefully through serial histological preparations. The length and width for each histological section was measured using slide micrometer (4 cm & 3 cm) respectively.The different stages of oocyte developmental stages were counted and analyzed in each season through One Way Analysis of Variance (ANOVA) with p<0.05 and Tukey’s Multiple Comparison Test. This calibrations clarified that the oogonia predominate the ovary during winter season, the previtellogenic oocytes predominate the ovary during spring season, the vitellogenic oocytes predominate the ovary during summer season. The majority of autolyzed oocyte were observed during winter season.